Plan de la rivière d'Albanie dans la baye de Hudson / par Samuel Hearne, 1774. - Hearne, Samuel, 1745-1792. (William L. Clements Library Image Bank, 1799)
Shows mouth of Albany River at Hudson Bay.; Copy 2 in: Hearne, Samuel. Voyage de Samuel Hearne. Paris. 1799.